Pengaruh Corporate Social Responsibility terhadap Corporate Image Nasmoco (Studi Kasus pada Warga Kota Semarang) - Widiyasari, Nurul Ami; Nugraha, Hari Susanta; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2015)
This research is aimed to analyze the influence of CSR of field economic, social and environmental of the corporate image toward Nasmoco. The population in this research is community of Semarang City whose feel the impact of CSR Nasmoco activities. Sampling is taken by proportional sampling technique. The sample size in this research were 160 respondents and only 100 respondents are qualified. Data analysis is performed by correlation, simple and multiple regression analysis, coefficients test of determination (R2), while hypothesis is tested by using the t test and f test. The results of this research indicate that the CSR field of economic, social and environmental dimension affected the corporate image of Nasmoco. From three variables which is studied, the CSR field of economic has greater influence on the corporate image of Nasmoco compared to the CSR field of social and environment.